Effectiveness of the Various Mechanisms and Practices in Preventing and Resolving Individual Labour Conflicts in Romania - Braica, Alexandra; Mesaros, Serghei (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
In our country, the practice of individual labour dispute resolution shows that it predominantly appeals to the courts, to the detriment of alternative mechanisms for individual labour dispute prevention and resolution. Therefore, we believe the focus should be on developing those practices and mechanisms, on the one hand to prevent the emergence of a labour dispute, and on the other hand to steer the conflict settlement through mediation. This paper refers to the existing situation in Romania, in terms of legislation and practice in the field. Promoting programs to increase the institutional capacity of social partners for resolving labour disputes, both individual and collective, would be an approach in accordance with the principles of social dialogue and would really contribute to developing a culture of social dialogue in Romania.